Building effective fishery ecosystem plans. (June 2018) - Levin, Phillip S.; Essington, Timothy E.; Marshall, Kristin N.; Koehn, Laura E.; Anderson, Lee G.; Bundy, Alida; Carothers, Courtney; Coleman, Felicia; Gerber, Leah R.; Grabowski, Jonathan H.; Houde, Edward; Jensen, Olaf P.; et al.
Abstract: U.S. fisheries management has made tremendous strides under the current management framework, which centers on single stocks rather than ecosystems. However, conventional management focuses on one fishing sector at a time, considers a narrow range of issues, and is separated into individual fishery management plans often leaving little opportunity to consider overarching management goals across fisheries. Ecosystem-based Fisheries Management (EBFM) provides mechanisms to address these but has not been widely adopted. Here, we review and analyze the development of Fisheries Ecosystem Plans (FEPs) as a means to implement EBFM. In doing so, we provide a blueprint for next-generation FEPS that have the potential to translate EBFM to action. We highlight FEPs as a structured planning process that uses adaptive management to operationalize EBFM. This "FEP Loop" process starts by identifying the key factors that shape a fishery system and considering them simultaneously, as a coherent whole. It then helps managers and stakeholders delineate their overarching goals for the system and refine them into specific, realistic projects. And it charts a course forward with a set of management actions that work in concert to achieve the highest-priority objectives. We conclude that EBFM is feasible today using existing science tools, policy instruments, and management structures. Not only that, nearly all of the steps in the proposed "FEP Loop" process are presently being carried out by U.S. fishery managers. The process of reviewing regional experiences in developing and applying the FEP loop will lead to adaptations and improvements of the process we propose. Highlights: Ecosystem-based Fisheries Management (EBFM) addresses shortcomings in fisheries management. EBFM is not widely practiced. Fisheries Ecosystem Plans (FEPs) provides a means to translate EBFM into action. provide a blueprint for next-generation FEPS that have the potential to translate EBFM to action. FEPs can be a planning process that uses adaptive management to operationalize EBFM. All steps in the proposed FEP process can be carried out by U.S. fishery managers.